Discussion on Problem and Methods of Monitoring Sediment Deposition of Warping Dams in Loess Plateau - Jianguo Zhang; Yawei Dong; Jingjing Li; Qiang Zuo (Shuitu baochi tongbao)
[Objective] A scientific monitoring methods for sediment-retaining amount in check dams were studied in order to provide practical support for accurately obtaining the sediment-retaining amount, and to realize the safe operation of check dams and the benefits of silt retaining. [Methods] Taking the Loess Plateau as the study area, the monitoring importance and existing problems of sediment-retaining amount in check dams were summarized, and the remote sensing monitoring methods of silt retaining in dam siltation for the Loess Plateau were proposed. [Results] The mainly influencing factors of obtaining sediment retention and siltation amount of check dam using remote sensing technology were proposed. The accuracy and feasibility of unmanned aerial vehicle (UAV) orthophoto measurement, UAV tilt photography, UAV lidar, and other remote sensing methods were compared and analyzed, as well as different application scenarios in silt detention and siltation monitoring in check dams. [Conclusion] Remote sensing technology has great advantages in sediment-retaining amount monitoring in check dams compared with mannual method, which can meet different needs for monitoring of silt trap and siltation. Remote sensing is an important development direction for measuring of sediment-retaining amount in check dams in the future.